Royal spin : a novel [large type] - Scobie, Omid; Benway, Robin (William Morrow Large Print, 2026)
She can handle the press...but can she handle the Palace? With the British monarchy reeling from a wave of scandals, young American politico Lauren Morgan is plucked from the White House press office to breathe new life into the Buckingham Palace communications team and improve the royal family's streak of bad headlines. But the Palace is an institution steeped in tradition and strict protocol, and Lauren quickly discovers that change is far from easy, or welcome, especially when you're dealing with culture clashes, displeased royal aides, and a risky new love interest--or two. Just as Lauren finds her footing at work--and with a charming royal reporter who may be more than just a press contact--an unexpected encounter from her past threatens the career she's worked so hard to build. And when scandal looms over the dashing duke who Lauren has developed a special bond with, she finds herself torn between duty, loyalty, success, and happiness.